2023
DOI: 10.5937/afmnai40-37560
|View full text |Cite
|
Sign up to set email alerts
|

Required personal protective equipment for prehospital healthcare provider in COVID-19 pandemic: A systematic review

Abstract: Aims. Coronavirus Disease 2019 (COVID-19) is a highly contagious disease, and a variety of personal protective equipment (PPE) has been recommended as preventive measures for prehospital emergency personnel, which has led to considerable challenges and a great confusion for the personnel. This review aims to identify different types of PPE required in the care of COVID-19 patients in prehospital emergency system. Material and methods. This study was carried out by searching through databases including: Pubmed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The coordination and summoning of other relief agencies is the responsibility of the EMS provider at the scene of the accident. Another stress-reducing factor among EMS providers is prioritizing personnel safety and using personal protective equipment during missions [ 35 , 36 ]. EMS providers often have limited information about their patients, work under uncontrolled conditions, and accompany their patients in confined ambulance spaces [ 19 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordination and summoning of other relief agencies is the responsibility of the EMS provider at the scene of the accident. Another stress-reducing factor among EMS providers is prioritizing personnel safety and using personal protective equipment during missions [ 35 , 36 ]. EMS providers often have limited information about their patients, work under uncontrolled conditions, and accompany their patients in confined ambulance spaces [ 19 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study conducted by Sanlıtürk, one of the stressors identified among nurses was the lack of personal protective equipment [ 39 ]. The issue of a lack of personal protective equipment (PPE) in Iran and in almost all countries, especially during the COVID − 19 pandemic, has been highlighted and is considered a significant source of stress in this profession [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basis of diseases caused by these viruses is acute respiratory infections with high contagiousness and lethality. The study of the multi-year history of coronaviruses does not provide final responses to the question of the emergence of the coronavirus disease 2019 in the human population (1,2). COVID-19 is caused by the coronavirus of severe acute respiratory syndrome-2 (SARS-COV-2), which was first discovered in Wuhan, China.…”
Section: Introductionmentioning
confidence: 99%